La planeación financiera y su relación con los procesos administrativos de la cooperativa de producción cafetalera los Angeles, parroquia San Carlos, año 2015 - Lucas Ponce, Evelyn Luisana (2015)
The companies now plan their finances in order to have clear ideas to invest their resources effectively and efficiently, analyze financial statements to evaluate alternatives and choose the most appropriate at key times to increase their profitability A financial planning is a strategy used for the knowledge of the economic and financial situation in order to be helpful in making the right decisions, but projections are not safe because companies are handled in a political, commercial and economic environment, is it is subject to government and prone to the effects of the economic crisis in a country decisions. The variable described as an object of research is the financial planning and its relationship with the administrative processes of the Production Cooperative Cafetalera Los Angeles, located in St. Charles Parish, Canton Quevedo, Los Rios Province, 2015 for the purpose of serving as a strategy to increase profitability and decision making to control the resources of the entity. In developing research methods they were used such as , observation used to gather information directly, deductive was used to examine the instruments of research and inductive applied to the formulation of the questions concerning the research helped the realization SWOT . These methods facilitated obtaining necessary data.